Measuring the effect of heterogeneity and trust on cooperation in common-pool resources - Van Klingeren, F (2021)
In this doctoral thesis I measure the effect of economic and sociocultural heterogeneity on cooperation through trust in the context of common-pool resources, using different techniques. The thesis is made up of three separate papers that are all trying to answer the same overarching question: how and to what extent does heterogeneity affect cooperation between appropriators of common-pool resources, and what is the role of trust in this process? The first paper applies innovative imputation techniques to use the famous CPR Database, compiled by the Nobel- prize winner Elinor Ostrom, to its full potential. The second paper uses data from a CPR laboratory experiment conducted in the United Kingdom and the Netherlands, in which a cooperation dilemma is simulated that is experienced in fishing grounds. The third paper uses data from the earlier experiment and an additional CPR experiment conducted in India, and analyses and interprets the difference in behaviour between the two experiments by using player type classification and agent-based models. Findings of this thesis suggest that heterogeneity does not necessarily impact cooperation negatively: sociocultural heterogeneity is not found to be negatively related to cooperation, economic heterogeneity is found to be positively related to cooperation under certain conditions and the combination of economic and sociocultural heterogeneity is found to be positively or negatively related to cooperation in CPRs depending on the operationalisation of sociocultural heterogeneity. In addition, it is found that trust has a positive effect on cooperation and that heterogeneity may impact trust negatively under some conditions.